Global differences in current strength and conditioning practice within soccer - McQuilliam, S. J.; Clark, D. R.; Erskine, R. M.; Brownlee, T. E. (International Journal of Sports Science & Coaching, 2024)
Differences exist between top-tier soccer leagues (e.g. anthropometry and match demands), which may influence strength and conditioning (S&C) practice. Thus, the aim of this study was to investigate whether current S&C practice in men's and women's (first team and academy) squads differed between global regions. A total of 170 participants, involved in the delivery of S&C support at their soccer club (based on South America (SA), the USA, the UK, or other European countries (EUR)), completed a survey examining their S&C methods. The survey comprised six sections: (i) academic qualifications and S&C coaching experience; and their preferred methods for (ii) physical testing; (iii) strength and power development; (iv) plyometric training; (v) speed development; and (vi) periodization. Coaches in EUR conducted fewer formal S&C sessions, placed less importance on free-weight resistance training (RT), and performed less speed and plyometric training compared to coaches in other global regions (all p < 0.05). While coaches working with UK squads devoted more time to physical development than those in EUR, they regarded bodyweight training as the most important RT modality in comparison to USA and SA, who prioritized free-weight RT. Finally, SA academy players are introduced to formal S&C later (~14 years old) than those in the UK (~12 years old, p = 0.002). However, it is reasonable to suggest that the S&C practice of coaches in the USA and SA align better with scientific guidelines for strength and power development in soccer, with emphasis on free-weight RT alongside regular sprint and plyometric training, compared to coaches in the UK and EUR.